'Whiny, Fake, and I Don't Like Her Hair': Gendered Assessments of Mayoral Candidates. Issue 4 (July 2023) - Tolley, Erin; Lawlor, Andrea; Fortier-Chouinard, Alexandre
Municipal mayoral elections present a compelling puzzle: what happens when gendered stereotypes about level of government conflict with those about type of office? Although local politics is viewed as communal and more feminine, the mayoral office is a prominent, prestigious position of political leadership that voters may perceive as more masculine. We intervene by analyzing open-ended comments about 32 mayoral candidates from a survey of 14, 438 municipal electors in eight Canadian cities. We argue gendered trait and issue stereotypes are embedded in voters' assessments of mayoral candidates. We find no evidence that female candidates benefit from their perceived competence in local policy issues, and they experience backlash when they display the traits typically associated with strong leaders. We conclude that, even at the level of government frequently thought of as more open to women, female mayoral candidates are disadvantaged by an enduring association between masculinity and political leadership.